The Management of Students at SMA Negeri 3 Panyabungan Mandailing Natal Regency - Sapirin Sapirin (STAI Miftahul Ula Nganjuk, 2025)
This study provides a descriptive analysis of student management at SMA Negeri 3 Panyabungan, located in Mandailing Natal Regency, North Sumatra. A qualitative research method with a phenomenological approach was employed to gather in-depth insights into the student management system. The findings reveal that SMA Negeri 3 Panyabungan effectively implements student management processes aimed at fostering the academic, social, and character development of its students, ultimately producing high-quality graduates. The student management system comprises four key components: planning, development, evaluation, and student transfers. The planning phase focuses on establishing the criteria, quality, and quantity of new students to be admitted, ensuring alignment with the school’s educational goals. Student development and guidance activities play a vital role in shaping students into individuals with strong character and academic competence, in line with the school's vision and mission. Regular evaluation is conducted to monitor the alignment between established standards and achieved outcomes, providing crucial feedback for continuous improvement. The study emphasizes the importance of optimizing both academic and non-academic programs and activities that focus on student services, ensuring that students receive comprehensive support throughout their educational journey. This research highlights the significance of an integrated student management system that nurtures well-rounded individuals prepared for the challenges of higher education and the workforce.